Optimization of gamma irradiation doses (60Co) for mutagenesis in strawberry (Fragaria × annanasa Duch) cv. Winter Dawn - Rodge, Rahul R; Karadak, S M; Bhosale, D N; Wagh, A M; Patil, Nirmal; Sharma, Sunny; Sharma, Jyoti; Chaudhuri, Madhurima; Jabroot, Khan; Kaur, Harjinder; et al. (Plant Science Today, 2025)
Strawberry, a vegetatively propagated crop, exhibits limited genetic variation, which constrains its adaptability and improvement potential. Gamma-ray radiation is a promising approach for enhancing genetic diversity and improving strawberries. Strawberry runners of the Winter Dawn cultivar were irradiated using 60Co, with doses ranging from 20 Gy to 40 Gy administered at a consistent rate of 1.52 Gy per minute to evaluate mutagenic effects. The survival effects in gamma irradiation-treated runners were recorded at 30 days after transplantation. An LD50 analysis was conducted to assess physiological impacts, and the lethal dose value was found to be 40 Gy, resulting in 50% mortality. Distinct differences in survival rates were observed between treated and untreated runners, with the highest survival rate (88%) at 20 Gy. The 30 Gy dose-treated runners exhibited the highest growth parameters, including crown diameter (14.32 mm), primary root length (29.50 cm), secondary root length (5.5 cm), and number of roots (39.6). Among fruit quality traits, maximum fruit length (39.84 mm), and fruit diameter (27.80 mm) were observed in runners treated with a 30 Gy gamma irradiation dose. Significant variations in survival, growth, and fruit quality were observed across different gamma irradiation doses. These findings provide a foundation for future efforts to develop potential strawberry mutants with improved traits through gamma irradiation. These findings provide a foundation for future efforts to develop potential strawberry mutants with improved traits through gamma irradiation.